Who owns nature? - Mira Bohórquez, Paula (Estudios de Filosofía, 2022)
Who owns nature? The answer to this question opens the way to a series of investigations on the civilizational crisis generated by human beings, which we echo in this issue. The question, from its philosophical point of view, considers both our understanding as human beings and the foundations of the current civilization, which has created a wide justificatory repertoire, from which it legitimizes the monopolization, exploitation and enslavement of all non-human nature.